Enhancing TVET blended learning student engagement through geo-attendance - Kamal Baharin, Safiza Suhana; Abd Aziz, Maslita; Othman, Zahriah; Md. Bohari, Nor Mas Aina (2024)
Blended Learning in Technical and Vocational Education and Training (TVET) contexts provides flexibility but frequently faces issues in retaining student engagement. This study introduces the Blended Attendance and Learning Analysis System (BALAS), a geo-attendance platform that uses spatial and demographic data to provide meaningful insights into student participation. The course combined synchronous and asynchronous sessions over five weeks, with attendance data from 83 students analyzed using GIS tools (i.e. Survey123) and ArcGIS dashboards. The study used heat maps and interactive dashboards to uncover key trends and challenges in a five-week blended learning program. The results from geospatial analysis showed that 65% of students living near UTeM actively participated in sessions, compared to only 35% of remote students, primarily due to limited internet connectivity. This study highlights the importance of tailored strategies, such as improved internet infrastructure and hybrid engagement models, to address disparities and optimize the learning experience for remote learners. The findings emphasize the potential of geo-attendance tools like BALAS to provide actionable insights for educators, helping design targeted interventions to enhance participation and equity in blended learning environments.